"It's in our DNA": perspectives on co-producing services in the UK voluntary sector. (1st March 2022) - Hannibal, Claire; Martikke, Susanne
Abstract : In this paper we report on the perceptions of co-production in the UK voluntary, community and social enterprise sector from those directly involved. We conducted five case studies, each involving interviews with two people who had formed a co-production relationship. We found positive perceptions of co-production from all interviewees. We suggest organisational and individual factors that are important to successful co-production and provide practical examples. We reflect on implications for practice by considering co-production relationships, time and resources.